2013
DOI: 10.1097/qad.0b013e32835a9984
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HIV–HBV coinfection in a multinational HIV-infected cohort

Abstract: Objective To understand the HIV-hepatitis B virus (HBV) epidemic from a global perspective by clinically and virologically characterizing these viruses at the time of antiretroviral therapy (ART) initiation in a multi-national cohort. Methods and design HIV-infected subjects enrolled in two international studies were classified as HIV-HBV co-infected or HIV monoinfected prior to ART. HIV-HBV co-infected subjects were tested for HBV characteristics, hepatitis D virus (HDV), a novel non-invasive marker of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
67
4
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 24 publications
13
67
4
2
Order By: Relevance
“…Reports indicate that HIV-positive patients infected with HCV and/ or HBV have increased risk of liver disease worldwide [6]. An increase in the rate of progression of HIV infection to AIDS has been reported among HIV-positive patients with HBV and/or HCV infection [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Reports indicate that HIV-positive patients infected with HCV and/ or HBV have increased risk of liver disease worldwide [6]. An increase in the rate of progression of HIV infection to AIDS has been reported among HIV-positive patients with HBV and/or HCV infection [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[912] Thus, the long-term efficacy of lamivudine-based ART in resource-limited settings may be different than in resource-rich settings. A Thai study of 11 HBeAg-negative and 19 HBeAg-positive HIV-HBV co-infected subjects taking lamivudine-based ART for up to 5 years found that all the HBeAg-negative subjects maintained suppression (HBV DNA <150 IU/ml) and none developed lamivudine-resistant HBV.…”
Section: Introductionmentioning
confidence: 99%
“…Although CP mutations may enhance HBV replication (28), several clinical reports have revealed that the presence of 1762T/1764A mutation is not always associated with the high HBV-DNA levels (29). In the study of Chilo L. et al, CD4 counts of patients with HIV/HBV infection were significantly lower than mono-infected patients (30). Another study also demonstrated low amount of CD4 cells in co-infected patients (31).…”
Section: Discussionmentioning
confidence: 97%